Quality improvement in allied healthcare: Key recommendations for educational institutions - Jithin Kalathikudiyil Sreedharan (18268894) (2023)
Allied Healthcare encompasses various professions involved in diagnosing, evaluating, and preventing diseases and disorders. Allied Healthcare Institutes (AHIs) provide education and training in these professions. However, there is currently a lack of explicit guidelines for ensuring quality excellence in AHIs. This narrative review aims to address this gap by examining existing literature on quality assurance in AHIs and proposing a conceptual framework that outlines essential components for establishing a high-quality AHI. A comprehensive search of PubMed and Google Scholar electronic databases yielded 86 relevant articles, which were analyzed and grouped into Nine themes related to the study's objectives. These themes include leadership in AHIs, student selection and support, teaching quality, curriculum development, research opportunities, stakeholder involvement, quality improvement initiatives, the impact of accreditation/certification, and physical facilities. Based on the review, the study presents 33 carefully formulated recommendations. By implementing these guidelines, policymakers and those interested in establishing AHIs can create institutions that promote the acquisition of new knowledge and skills, foster research and development, and provide excellent educational resources. Other Information Published in: Informatics in Medicine Unlocked License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://doi.org/10.1016/j.imu.2023.101412